2014
DOI: 10.1007/s12031-014-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

Time-Dependent Decrease of Clusterin as a Potential Cerebrospinal Fluid Biomarker for Drug-Resistant Epilepsy

Abstract: Our previous study on proteomic analysis has shown that clusterin (CLU) is significantly decreased in the cerebrospinal fluid (CSF) of patients with epilepsy. Therefore, the present study aimed to confirm CLU concentration reduction in the CSF of patients with drug-resistant epilepsy and drug-responsive epilepsy. Fifty-two patients with epilepsy (23 drug resistance and 29 drug effectivity) and 20 control individuals were recruited. The concentrations of CSF and serum CLU were detected. Moreover, alteration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Additionally, according to Yu et al. (30), the CLU concentration was decreased in the CSF of human models diagnosed with epilepsy. Therefore, measurement of CLU concentrations in the CSF may be helpful in generating differential diagnosis of neurodegenerative disorders (31).…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, according to Yu et al. (30), the CLU concentration was decreased in the CSF of human models diagnosed with epilepsy. Therefore, measurement of CLU concentrations in the CSF may be helpful in generating differential diagnosis of neurodegenerative disorders (31).…”
Section: Discussionmentioning
confidence: 92%
“…For instance, previous studies of patients with epilepsy demonstrated increased clusterin mRNA expression levels in the temporal lobe tissue 47 . Still, several epilepsy studies have shown a 20–30% reduction in serum clusterin levels in patient with “idiopathic temporal lobe epilepsy” or “idiopathic epilepsy” 27,28 . So far, none of the previous studies has analysed clusterin as a biomarker for post-traumatic epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…87-92 Neuronal and oligodendrocyte apoptosis occur in human cervical spondylotic myelopathy 93 and canine CSM 94 , and are implicated in disease progression. 3 The lower CSF clusterin concentrations identified in CSM-affected dogs may compromise neuronal and oligodendrocyte survival by promoting apoptosis.…”
Section: Discussionmentioning
confidence: 99%